Relaxin-3 Innervation From the Nucleus Incertus to the Parahippocampal Cortex of the Rat - García-Díaz, Cristina; Gil-Miravet, Isis; Albert-Gasco, Hector; Mañas-Ojeda, Aroa; Ros-Bernal, Francisco; Castillo-Gómez, Esther; Gundlach, Andrew L.; Olucha-Bordonau, Francisco E. (Frontiers in Neuroanatomy, 2021)
Spatial learning and memory processes depend on anatomical and functional interactions between the hippocampus and the entorhinal cortex. A key neurophysiological component of these processes is hippocampal theta rhythm, which can be driven from subcortical areas including the pontine nucleus incertus (NI). The NI contains the largest population of neurons that produce and presumably release the neuropeptide, relaxin-3, which acts via the Gi/o-protein-coupled receptor, RXFP3. NI activation induces general arousal including hippocampal theta, and inactivation induces impairment of spatial memory acquisition or retrieval. The primary aim of this study was to map the NI/relaxin-3 innerva-tion of the parahippocampal cortex, including the medial and lateral entorhinal cortex, endopiriform cortex, perirhinal, postrhinal and ectorhinal cortex, the amygdalohippocampal transition area and posteromedial cortical amygdala. Retrograde tracer injections were placed in different parts of the medial and lateral entorhinal cortex, which produced prominent retrograde labeling in the ipsilateral NI and some labeling in the contralateral NI. Anterograde tracer injections into the NI and im-munostaining for relaxin-3 produced fiber labeling in deep layers of all parahippocampal areas and some dispersed fibers in superficial layers. Double-labeling studies revealed that both hippocam-palprojecting and calcium-binding protein-positive (presumed GABAergic) neurons received a relax-in-3 NI innervation. Some of these fibers also displayed synaptophysin immunoreactivity, consistent with the presence of the peptide at synapses; and relaxin-3-positive fibers containing synaptophysin boutonlike staining were frequently observed in contact with hippocampal-projecting or calcium-binding protein-positive neuronal somata and more distal elements. Finally, in situ hybridization stud-ies revealed that entorhinal neurons in the superficial layers, and to a lesser extent in deep layers, con-tain RXFP3 mRNA. Together, our data support functional actions of the NI/relaxin-3-parahippocampal innervation on processes related to memory, spatial navigation and contextual analysis.